Detection and measurement of fetomaternal haemorrhage: serum alpha-fetoprotein and the Kleihauer technique. Issue 6073 (28th May 1977) - Lachman, E; Hingley, S M; Bates, G; Ward, A M; Stewart, C R; Duncan, S L
Abstract : A raised maternal serum alpha-fetoprotein concentration was taken as an indicator of fetomaternal haemorrhage due to amniocentesis and was used to calculate the volume of the fetal bleed. The alpha-fetoprotein concentration seemed to be a more sensitive and reliable indicator than the established Kleihauer technique and may have further applications in antenatal testing.